Meningkatkan Tujuan Pembelajaran Siswa dengan Konsep Pilar Pendidikan Unesco di Era Merdeka Belajar - Elis Sahmiatik; Hamsyin Basri; Eva Latipah (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This article attempts to harmonize the results of Sternberg’s research with the four pillars of education that Unesco proclaimed as an educational concept that can optimize students abilities in carrying out their roles in the community. This article offers three formulations: (1) is learning the main goal for all students? (2) what is the concept of the four pillars of education launched by Unesco? (3) why do students learning objectives in the era of independent learning need to be improved?. This article is a qualitative research type of literature (library research) with data collection techniques, namely the indentification of discourse from sources, in the form of articles, journals and books that are relevant to the main source of this research, namely the the results of the book review Innovation in Edu Psychology by Sternberg on the results of the Student goals research that done by Siegler et al. the results of the study indicate an understanding of the concept of Unesco’s education pillars which can be used as a basis for education actors to improve learning objectives.